Relationship between growth differentiation factor 15 and functional prognosis and severity in traumatic brain injury - Hiroshi Ito; Takeshi Ebihara; Hisatake Matsumoto; Jun Oda (Scientific Reports)
Abstract Circulating growth differentiation factor 15 (GDF-15) increases in response to inflammation and tissue damage. Its association with functional prognosis in cerebral infarction and subarachnoid hemorrhage is established; however, its role in traumatic brain injury (TBI) and its relationship with Sequential Organ Failure Assessment (SOFA) score, an indicator of systemic organ damage in TBI, remains unclear. This study aimed to explore the correlation between GDF-15 and functional outcomes at discharge in patients with TBI and stroke, including its association with SOFA scores in TBI. Patients with cerebral infarction, subarachnoid hemorrhage, and TBI transported within 24 h from July 2020 to August 2022 were included. Multivariable logistic regression analyzed the relationship between GDF-15 levels at admission and functional outcomes at discharge, with age and sex as covariates. Additionally, correlations between GDF-15 levels and SOFA scores were assessed. Multivariable logistic regression showed a relationship between GDF-15 levels at admission and functional outcomes at discharge in cerebral infarction and subarachnoid hemorrhage but not in TBI. In TBI cases, GDF-15 correlated with SOFA scores, indicating its potential as a TBI severity marker. Although functional prognosis at discharge was evaluated, long-term outcomes were not clear, and this will be addressed in future research.